2017
DOI: 10.1002/cbic.201700006
|View full text |Cite
|
Sign up to set email alerts
|

Activity‐Based Probes for HECT E3 Ubiquitin Ligases

Abstract: Activity‐based probes (ABPs) have been used to dissect the biochemical/structural properties and cellular functions of deubiquitinases. However, their utility in studying cysteine‐based E3 ubiquitin ligases has been limited. In this study, we evaluate the use of ubiquitin‐ABPs (Ub‐VME and Ub‐PA) and a novel set of E2–Ub‐ABPs on a panel of HECT E3 ubiquitin ligases. Our in vitro data show that ubiquitin‐ABPs can label HECT domains. We also provide the first evidence that, in addition to the RBR E3 ubiquitin lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 68 publications
0
20
0
Order By: Relevance
“… 7 , 18 We then turned to the biochemical Ub-PA (ubiquitin-propargylamide) assay. In this assay, the catalytic domain of USP14 (USP14 CAT ) was preincubated with IU1, followed by addition of the covalent inhibitor Ub-PA. 19 22 The covalent attachment of Ub-PA (8 kD) to USP14 CAT (45 kD) produced the novel USP14/Ub-PA complex with an increased molecular weight (53 kD). We observed that at a 5 mM concentration IU1 significantly inhibited the formation of the USP14/Ub-PA complex (Fig.…”
Section: Resultsmentioning
confidence: 99%
“… 7 , 18 We then turned to the biochemical Ub-PA (ubiquitin-propargylamide) assay. In this assay, the catalytic domain of USP14 (USP14 CAT ) was preincubated with IU1, followed by addition of the covalent inhibitor Ub-PA. 19 22 The covalent attachment of Ub-PA (8 kD) to USP14 CAT (45 kD) produced the novel USP14/Ub-PA complex with an increased molecular weight (53 kD). We observed that at a 5 mM concentration IU1 significantly inhibited the formation of the USP14/Ub-PA complex (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Virdee et al demonstrated an application in profiling primary fibroblasts from Parkinson's disease patients. Licchesi and co-workers (Byrne et al, 2017) later showed these probes react with NEDD4, UBE3C and HECTD1.…”
Section: Ubiquitin-protein Probes For E3 Ligasesmentioning
confidence: 93%
“…Monoubiquitin probes have been demonstrated to label ubiquitin conjugation machinery (Kamadurai et al, 2009;Love et al, 2009;Kim et al, 2011;Ekkebus et al, 2013;Maspero et al, 2013;Byrne et al, 2017) however they lack specificity. Tan and co-workers (Lu et al, 2010) developed E1 targeting probes by mimicking the adenylate intermediate formed in the E1 active site.…”
Section: Ubiquitin-adenine Probesmentioning
confidence: 99%
“…Thus, the E3 was named a RING-Cys-relay E3, and it is the first E3 shown to have a preference for Thr ubiquitination. Similar design of E2-UB conjugates with an acrylamide linker as a Cys trap has been used to probe HECT E3 activity in cell lysates (Byrne et al, 2017). E2-UB probes demonstrate the power of protein engineering to generate customized tools to discover new cellular protein ubiquitination activities.…”
Section: B Activity-based Probes For Ubiquitin-transferringmentioning
confidence: 99%